2022
DOI: 10.1002/cche.10580
|View full text |Cite
|
Sign up to set email alerts
|

Uncooked rice consumption: Causes, implications, regulation, and interventions

Abstract: Background and Objectives Uncooked rice is not classified as produce under the Food Safety Modernization Act (FSMA) of the United States Food and Drug Administration produce safety rule because it is considered a food grain that is typically processed before consumption. However, uncooked rice is eaten by members of the raw food movement, pregnant pica patients, refugees in war zones, and young women as a perceived beauty treatment. Findings The consumption of raw rice may pose serious health risks such as foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…In addition, we previously showed that SYP4 showed antifungal efficacy and was non-cytotoxic to canine red blood cells [22]. Therefore, cooked Sangyod rice can be safely used for consumption by humans or animals with gastrointestinal diseases to prevent bacterial infection and suppress the virulence factors from gastrointestinal pathogens [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we previously showed that SYP4 showed antifungal efficacy and was non-cytotoxic to canine red blood cells [22]. Therefore, cooked Sangyod rice can be safely used for consumption by humans or animals with gastrointestinal diseases to prevent bacterial infection and suppress the virulence factors from gastrointestinal pathogens [57,58].…”
Section: Discussionmentioning
confidence: 99%